Prevention of dental caries with remineralization in containing Casein Phosphopeptid-Amorphous Calcium Phosphate (CPP-ACP) to students SD Swasta Muhammadiyah – 03 Medan - Batubara, Fitri Yunita; M. Zulkarnain; Cut Nurliza; Nurdiana; Dewi Kartika (ABDIMAS TALENTA: Jurnal Pengabdian Kepada Masyarakat, 2019)
Dental caries is an infectious disease caused by demineralization of enamel and dentin which is closely related to the consumption of cariogenic foods. Generally children entering school age have a high caries risk, because at this school age children usually like food and drink snacks as they wish. The impact that occurs when since the beginning has experienced caries is in addition to the function of the teeth as chewing that is disrupted, swollen gums, the child will also experience disturbances in carrying out their daily activities, so the child will not eat and consequently malnutrition can occur, this causes the child to be unable to study because of lack of concentration so that it will affect intelligence. The results of the field analysis and preliminary interviews with school leaders as partners in community service obtained data that students in Muhammadiyah Private Elementary School 03 Medan aged 6-8 years experienced dental caries with the characteristics of cavities, porous, and stains / plaques. These characteristics are related to the patterns or behavior of students who like to consume sweet foods like candy, bread, and chocolate. School Dental Health Efforts (UKGS) have also not been implemented in schools. Therefore, community service is needed to be carried out with a form of socialization prevention for early caries in order to provide knowledge of the main causes, ways of spreading, impact, efforts to prevent dental caries, and providing remineralization (dental caries prevention) containing Casein Phosphopeptid-Amorphous Calcium Phosphate (CPP-ACP) to students of grade II Muhammadiyah Primary School 03 Medan. Community service activities were carried out by five service teams from the Faculty of Dentistry, University of North Sumatra on August 27, 2019, involving as many as twenty two USU FKG students who were undergoing clinical clerkship. The socialization and provision of caries prevention materials to 111 students who were in grade II of Muhammadiyah Primary School - 03 Medan.